Combustion properties and pyrolysis kinetics of flame-retardant polyurethane elastomers. (February 2017) - Chen, Xilei; Huo, Lili; Liu, Jianbo; Jiao, Chuanmei; Li, Shaoxiang; Qian, Yi
Flame-retardant polyurethane elastomers (PUEs) have been prepared using trichloroethyl phosphate (TCEP) as flame retardant. The combustion performances and thermal decomposition properties of PUEs were studied using cone calorimetry test and thermogravimetric analysis, respectively. Kissinger method and Flynn–Wall–Ozawa (FWO) method were adopted to discuss the pyrolysis kinetics of PUEs. The experimental results showed that TCEP has good flame-retardant effect for PUE. With the increase of TCEP, the peak heat release rate and total heat release values decrease. A good diagram of linear regression can be obtained from both Kissinger and FWO methods. The activation energy values of flam- retardant PUE can be calculated from FWO method at different conversion rates.